Effect of prepubertal caffeine consumption and recovery on adult erectile tissue functions in Wistar rats - Shakiru Salami; Bashua Kassim; Michael Allen; Hussein Salahdeen; Babatunde Murtala (Acta Biologica Slovenica)
The study examines the impact of caffeine consumption during prepubertal development and recovery on the contractile function of the adult corpus cavernosum in Wistar rats. Prepubertal male rats consumed distilled water (vehicle) and caffeine (5 mg/kg). A third group consumed caffeine and was allowed a period of recovery. Cavernosa tissues were excised at adulthood, and their contractile functions in the presence of Ca2+, K+, indomethacin, glibenclamide, methyl blue, L-NAME, and sodium nitroprusside were assessed. K+-induced increase in contraction in the caffeine-treated group was similar to that in the recovery group. Ca2+ ions, however, increased contraction significantly in the caffeine group compared to the recovery group. Acetylcholine-mediated relaxation (%) was significantly higher in the recovery compared to the caffeine treated after incubation with indomethacin and methyl blue. Acetylcholine-mediated relaxation, however, was higher in caffeine as compared to the recovery group after incubation with glibenclamide and L-NAME. Relaxation in the presence of sodium nitroprusside was significantly reduced in recovery than in the caffeine-treated group. Prepubertal caffeine intake had an erectogenic effect on the cavernous tissues in the presence of glibenclamide, nifedipine, and L-NAME. Inhibitors of prostacyclin (indomethacin) and cGMP (methyl blue) militate caffeine-induced relaxation. Effects were reversed after recovery.